2012
DOI: 10.1186/1471-2164-13-562
|View full text |Cite
|
Sign up to set email alerts
|

The genome sequence of Propionibacterium acidipropionici provides insights into its biotechnological and industrial potential

Abstract: BackgroundSynthetic biology allows the development of new biochemical pathways for the production of chemicals from renewable sources. One major challenge is the identification of suitable microorganisms to hold these pathways with sufficient robustness and high yield. In this work we analyzed the genome of the propionic acid producer Actinobacteria Propionibacterium acidipropionici (ATCC 4875).ResultsThe assembled P. acidipropionici genome has 3,656,170 base pairs (bp) with 68.8% G + C content and a low-copy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
85
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 89 publications
6
85
0
1
Order By: Relevance
“…Targeted genetic engineering of propionibacteria remains challenging for several reasons: propionibacteria have a high GC content, which complicates genetic manipulation and contributes to poor gene annotations [58]; relatively few closed genomes are available [17,18]; a small number of cloning vectors are available [22,59,60]; the ability of strains to readily develop spontaneous antibiotic resistance; thick cell walls; and the presence of strong restriction modification systems which contribute to the low transformation efficiency of propionibacteria [61]. A number of recent studies have reported the modification of P. freudenreichii subsp.…”
Section: Genetic Engineering To Overcome the Current Challenges For Pmentioning
confidence: 99%
“…Targeted genetic engineering of propionibacteria remains challenging for several reasons: propionibacteria have a high GC content, which complicates genetic manipulation and contributes to poor gene annotations [58]; relatively few closed genomes are available [17,18]; a small number of cloning vectors are available [22,59,60]; the ability of strains to readily develop spontaneous antibiotic resistance; thick cell walls; and the presence of strong restriction modification systems which contribute to the low transformation efficiency of propionibacteria [61]. A number of recent studies have reported the modification of P. freudenreichii subsp.…”
Section: Genetic Engineering To Overcome the Current Challenges For Pmentioning
confidence: 99%
“…jensenii produces PA through the dicarboxylic acid pathway, with LA and AA as by-products (16). Several genomes of Propionibacterium have now been sequenced (3,25,(27)(28)(29)(30). However, genetic engineering of these bacteria has not been thoroughly investigated because of the difficulty in transforming Gram-positive bacteria, the various restriction-modification systems of these bacteria, the high GC content in their genomes, and the lack of cloning tools.…”
Section: Discussionmentioning
confidence: 99%
“…Pyruvate is converted to oxaloacetate and then to malate by malate dehydrogenase (MDH). Fumarate hydratase (FUM) catalyzes the conversion of malate to fumarate, which is converted to PA via a series of intermediates, namely, succinate, succinyl coenzyme A (CoA), methylmalonyl CoA, and propionyl CoA (25). This step is an NADH-consuming pathway.…”
mentioning
confidence: 99%
“…ACD from the phototrophic Chloroflexus aurantiacus has recently been purified, and the recombinant enzyme was characterized (20). The syntrophs Pelotomaculum thermopropionicum (21) and Syntrophus aciditrophicus (22) and the propionic acid-producing Propionibacterium acidipropionici (23) all lack genes for the PTA-ACK pathway and instead have acd genes. ACD has been identified via proteome analysis of P. acidipropionici cells grown under acetateproducing conditions, but the enzyme has not been purified or characterized (23).…”
mentioning
confidence: 99%
“…The syntrophs Pelotomaculum thermopropionicum (21) and Syntrophus aciditrophicus (22) and the propionic acid-producing Propionibacterium acidipropionici (23) all lack genes for the PTA-ACK pathway and instead have acd genes. ACD has been identified via proteome analysis of P. acidipropionici cells grown under acetateproducing conditions, but the enzyme has not been purified or characterized (23). Likewise, the acetate-producing archaea listed above that have ACD lack genes encoding the PTA-ACK pathway.…”
mentioning
confidence: 99%